Exploring the Use of Lectora Inspire Media in Learning Flat Buildings in Elementary School - Rahmati, Audia; Suparman, Tarpan; Fitri, Ayu (FKIP - Universitas Riau, 2025)
This study aims to determine how much impact Lectora Inspire-based learning media has on the development of student learning outcomes on the concept of composition and decomposition of flat shapes in grade IV SD Negeri Karangligar I, Karawang Regency, West Java. Using descriptive qualitative method, the study involved 19 students and homeroom teachers, collecting data through observation, interviews, documentation, and tests. The results showed that Lectora Inspire improved student learning, especially in the composition and decomposition of flat shapes, with higher enthusiasm and classroom interaction compared to conventional methods. Both teachers and students (especially high ability ones) responded positively, although medium and low ability students needed assistance. In conclusion, Lectora Inspire is recommended as an effective mathematics learning tool in primary schools.